POLYCYCLIC AROMATIC HYDROCARBON (PAH) LEVELS IN SLUDGES FROM WASTEWATER TREATMENT PLANTS IN BURSA - Salihoglu, N. Kamil; Salihoglu, Guray; Tasdemir, Yucel (YILDIZ TECHNICAL UNIV, 2011)
The purpose of this study was to investigate the polyaromatic hydrocarbons (PAHs) concentrations in sludge samples from urban and industrial wastewater treatment plants(WWTP) in Bursa city. Sludge samples were collected from 6 wastewater treatment plants in June 2008. The samples were ultrasonically extracted and PAH contents of the samples were measured by using GC-MS. The highest PAH level was observed in automotive industry WWTP sludge among the other industries. Urban WWTP sludge was in the second order with regards to the PAH levels. 5 and 6 ring PAH compounds were dominant in almost all sludge samples studied. The ratios of specific PAH compounds suggested that the PAHs in the sludge samples were combustion originated.
Keywords: Industry; treatment plant sludge; PAHs; ring numbers; Engineering